STUDY OF GENETIC DIVERSITY IN SYNTHETIC HEXAPLOID WHEATS USING RANDOM AMPLIFIED POLYMORPHIC DNA - A. Qadir; M. Ilyas; W. Akhtar; E. Aziz; A. Rasheed; T. Mahmood (Journal of Animal and Plant Sciences, 2015)
Ten Synthetic Hexaploid Wheats (SHWs) (2n = 6x = 42, AABBDD) were analyzed using 7 Randomly Amplified Polymorphic DNA (RAPD) primers to investigate the potential genetic diversity resided within the D-genome of common wheat. Total 190 fragments were amplified in which 141 were polymorphic showing 74 % of polymorphism. Polymorphism Information Content (PIC), Genetic Similarity (GS) Coefficient, and Principle Component Analysis (PCA) showed that D-genome of wheat contain sufficient genetic diversity. Cluster analysis based on Unweighted Pair Group Method with Arithmetic Mean (UPGMA) grouped the genotypes into two main clusters with similarity of 0.44 to 0.80 with an average of 0.62. Analysis of variance (ANOVA) exhibited ample amount of variability among the genotypes. The results indicated that synthetic hexaploid wheats are an efficient way to use the genetic variation of D-genome from Aegilops Squarrosa for wheat improvement. The results further established the efficacy and usefulness of RAPD marker for evaluation of genetic polymorphism and diversity present within Synthetic Hexaploid Wheats.
Keywords: Genetic diversity; D-genome; Synthetic hexaploid wheat; Polymorphism